The dream as self-deception in Seneca - Amaral, Ronaldo (Revista Archai, 2025)
In Greco-Roman antiquity, particularly within the realm of philosophical thought, dreams represent the interface between the mythical-religious and the psychic-rational, generally showing their point of intersection. As such, they tend to be beneficent, foreseeing tragedies or even enabling the application of healing therapies. However, they may also simply reflect the vicissitudes inherent to the psyche, indicating a state of confusion - either from the standpoint of a deviation or clouding of waking reason or, as its corollary, the inability to exercise knowledge and access reality. Seneca, as will be demonstrated here, is the spokesperson for this latter perspective.